2010
DOI: 10.1007/s00240-010-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

Urologists versus radiologists made PCNL tracts: the UK experience

Abstract: We aim to explore the practice of who makes the PCNL tract in the U.K. and Northern Ireland as well as presenting our data for two different approaches to PCNL tracts in Northern Ireland. A national questionnaire survey was carried out across the National Health Services hospitals in U.K. In addition, a retrospective analysis of 134 PCNL cases was carried out. Group I included 103 (77%) cases with urologist-made tracts, while group II included 31 (23%) cases with radiologists-made tracts. The survey suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…We found that only a very small proportion of PCNL procedures (~1%) were abandoned because of failed renal access. This failed access rate compares favourably with those previously reported elsewhere .…”
Section: Discussionmentioning
confidence: 99%
“…We found that only a very small proportion of PCNL procedures (~1%) were abandoned because of failed renal access. This failed access rate compares favourably with those previously reported elsewhere .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high stone free rates obtained in a single session; PNL could be associated with certain types of complications like bleeding, organ perforation and sepsis (12). Such complications could be encountered during all steps of PNL among which the access to the renal collecting system seems to be the most important one (13). Related to this subject, an appropriate initial puncture of the most desirable calyx of the kidney is extremely important for a successful and safe procedure by limiting the chance of both bleeding as well as injury to the surrounding organs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In percutaneous nephrolithotomy (PNL), the percutaneous technique of insertion of a small-caliber nephrostomy tube is used to access the kidney and drain an obstructed renal unit. Ever since its discovery, the percutaneous removal of kidney stone has replaced open techniques and is now being used with extracorporeal shockwave lithotripsy (SWL) in the clinical setting [1]. These newer techniques are far less invasive than open surgery.…”
Section: Introductionmentioning
confidence: 99%